Ultrafast plasmon dynamics and dephasing time in a single bowtie structure observed by time-resolved photoemission electron microscopy - Xu, Yang; Qin, Yulu; Wang, Guiqi; Ji, Boyu; Lang, Peng; Song, Xiaowei; Lin, Jingquan (SPIE, 2020)
Accurately grasping and controlling the plasmon dynamics and dephasing time is a prerequisite for the application of plasmons. Here, we report on the investigation of dynamics and dephasing time of different plasmonic hot spots in a single bowtie structure under varied light polarization using time-resolved photoemission electron microscopy (PEEM). In contrast to those previous global-parameter descriptions, we here report the experimental observation of apparently spatially diverse plasmon dynamic characteristics and spatially different dephasing time within a plasmonic bowtie. We experimentally obtain different plasmon dynamics in the tips of the bowtie nanostructure with different light polarization and actively control dephasing time by changing the light polarization which transforms the plasmon mode. Experimental results got the minimum dephasing time of 8.5fs and the maximum dephasing time of 17fs, which has a large adjustment range. In addition, we found that structural defects can prolong the dephasing time, and we analyzed its role in the influence of plasmon dynamics and dephasing time.